问题 解答题
脱式计算
3
8
÷[(
1
5
+
1
4
)×
3
8
]
3
5
-
4
5
×
1
6
÷
3
5

7
20
÷〔
7
11
×(5-
4
3
)〕
1
2
+
1
3
)÷
5
8
-
1
3

76.9÷[1÷(3.1-3.09)]
(0.72+6.58÷0.7)×0.5.
答案

(1)

3
8
÷[(
1
5
+
1
4
)×
3
8
]

=

3
8
÷[
9
20
×
3
8
]

=

3
8
×
160
27

=

20
9

(2)

3
5
-
4
5
×
1
6
÷
3
5

=

3
5
-
2
15
÷
3
5

=

3
5
-
2
9

=

17
45

(3)

7
20
÷[
7
11
×(5-
4
3
)]

=

7
20
÷[
7
11
×
11
3
]

=

7
20
×
3
7

=

3
20

(4)(

1
2
+
1
3
)÷
5
8
-
1
3

=

5
6
×
8
5
-
1
3

=

4
3
-
1
3

=1;

(5)76.9÷[1÷(3.1-3.09)]

=76.9÷[1÷0.01]

=76.9÷100

=0.769;

(6)(0.72+6.58÷0.7)×0.5

=(0.72+9.4)×0.5

=10.12×0.5

=5.06.

选择题
单项选择题